Investigation of 131I kinetics in the rats organism after a single intake - I. P. Drozd; A. I. Lypska; L. K. Bezdrobna; V. A. Shytiuk; O. A. Sova (Ядерна фізика та енергетика)
Kinetics of 131I in the organism of the laboratory rats is investigated after a single intake of various activities of isotopes. The isotope content is measured in different organs and tissues. Half-life of 131I has been determined. The specifics of the accumulation and excretion of the isotope from organism are discussed.